1995
DOI: 10.1111/j.1365-2362.1995.tb01741.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of colectomy with ileo‐anal anastomosis on the biliary lipids

Abstract: Total colectomy with ileo-anal anastomosis is an effective treatment for ulcerative colitis and familial adenomatous polyposis. The absence of the colon and the coexistence of bile acid malabsorption may increase bile lithogenicity, but data on biliary lipid composition in patients with this operation is lacking. Our aim was to assess bile lithogenicity, bile composition and mass of biliary lipids within the gallbladder. We studied 11 patients with total colectomy and ileo-anal anastomosis and 16 healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…Similar results were obtained from Einarsson’s group in patients with Crohn’s disease following ileal resection 25. Similarly, Koivisto and Miettilnen found cholesterol saturation of duodenal bile to be normal in patients with partial ileal bypass26 and we found this to be true also in patients with ileoanal anastomosis and total colectomy,27 who have bile acid malabsorption according to the 75 SeHCAT test 16…”
Section: Discussionsupporting
confidence: 87%
“…Similar results were obtained from Einarsson’s group in patients with Crohn’s disease following ileal resection 25. Similarly, Koivisto and Miettilnen found cholesterol saturation of duodenal bile to be normal in patients with partial ileal bypass26 and we found this to be true also in patients with ileoanal anastomosis and total colectomy,27 who have bile acid malabsorption according to the 75 SeHCAT test 16…”
Section: Discussionsupporting
confidence: 87%
“…In two other studies, no increased cholesterol saturation of duodenal bile was observed [12,14], and a recent study, in which gallbladder bile was obtained by direct puncture of the gallbladder, revealed that biliary lipid composition and cholesterol saturation of bile may be normal after colectomy [13]. Biliary composition, cholesterol saturation and nucleation were not investigated in our study, but (presumably due to the loss of bile acids in the intestine) the fractional turnover of bile acids was markedly increased suggesting an impairment of the enterohepatic circulation of bile acids.…”
Section: Discussionmentioning
confidence: 96%
“…It was assumed that impaired intestinal bile acid absorption was followed by formation of a more lithogenic bile and an increased incidence of cholelithiasis [5,6]. Other studies in colectomized patients, however, found normal biliary cholesterol saturation, normal biliary lipid composition and normal nucleation time [12,13,14]. Thus, the present investigation, which for the first time directly studied bile acid kinetics in patients after proctocolectomy and IPAA, contributes to the understanding of bile acid metabolism under this condition and its potential pathophysiologic sequelae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 Patients with IAA show a reduced biliary secretion of bile acids and reduced masses of cholesterol, bile acid, phospholipids. [21][22][23] In particular the deoxycholic acid is significantly reduced in patients with IAA. 20,24,25 This secondary bile acid is produced by the intestinal microflora containing 7a-dehydroxylase and it is considered as promoter of intestinal carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%